Easy access? Finding one's way from secondary to post-secondary music education and training in Australia - Bennett, Dawn; Lancaster, H.; O'Hara, B. (National Centre for Research in Music Education and Sound Arts, 2013)
Access to post-secondary music education and training in Australia is more diverse than ever before. In addition to universities and vocational education providers, a growing number of private and public providers deliver higher and vocational education; there is a vast range of non-accredited mentoring opportunities and internships; and a growing number of secondary schools offer post-secondary study prior to matriculation.Recognising these developments, the Music Council of Australia is currently mapping the range of post-secondary music education and training in Australia, cross-referencing these findings with current trends across the Australian Higher Education sector. This paper reports on initial findings from the first stage of this comprehensive audit of music education and training. With an emphasis on informing decision-making, the paper addresses the range of higher education programs currently available and the ease of access to, and transition between, secondary and post-secondary programs. Initial findings indicate a diverse range of study options and pathways, but also suggest that informed decision-making is a growing challenge for prospective students, mentors and parents.